Estudo de poli(organofosfazenos): síntese, caracterização, blendas políméricas e aplicações - Virginia Paula Rodrigues Silva (2008)
This work presents a study of polymeric blends based on polyphosphazenes as well as the syntheses of three new polyphosphazenes candidates to be studied asbiomaterials. The polymeric blends were prepared mixing poly[bis(methoxy-ethoxyethoxy) phosphazene] - MEEP and poly(ethylene oxide) - PEO, in the following concentrations: 12.5%; 37.5%; 50.0%; 62.5% and 87.5% w/w MEEP. The behavior of the blends was investigated by thermal analysis, X-ray diffraction, FTIR and AFM. Allthe blends presented glass two distinct glass transitions (Tg), detected by MDSC. An excess of melting enthalpy was observed in the blends containing 62.5% and 87.5% w/w MEEP indicating the formation of new organized structures after the formation of these blends. Both X-ray diffraction, AFM and FTIR indicated the intercalation of MEEP sidechains with the crystalline structure of PEO. Three new polyphosphazenes were synthesized: PMAPhos, PPrP and PLysP. PMAPhos formed a hydrogel after crosslinking reaction. This cross-linking reaction was monitored by FTIR collecting severalspectra in function of temperature. The temperatures were the modifications associated to reticulation reactions found in the spectra can be related to the temperatures observed in the DSC experiments for such reactions. The hydrogel formed presented both thermalandpH responsive behavior. At pH 8, the material presented a swelling degree of 3.000% compared to the dry sample. At higher pHs the hydrogel underwent a collapsing in its structure, although the polymer chains were charged, which was explained by the Donnans osmotic pressure equilibrium. The globule-coil transition temperature wasevaluated by DSC to be at 45 oC, and confirmed by an expansion experiment. PPrP and PLysP were synthesized and, according to preliminary characterization, a fully substitution was obtained in PLysP, but not in PPrP due to esterical hindrances. The Tgs found were -4 oC for PLysP and 56 oC for PPrP.